Desarrollo de una aplicación pedagógica como apoyo para la reducción de la violencia juvenil en instituciones educativas del Quindío (2023)
Evidenced violence in the educational context of the municipality of Armenia, Quindío, during the virtual approach of academic functions and activities in the contingency of confinement" is a research project currently underway by the Faculty of Psychology of the Antonio Nariño University, in collaboration with the Faculty of Systems Engineering, and whose purpose is to publicize the different types of violence that occur in primary and secondary educational institutions in the municipality of Armenia.